El continuo de la psicosis: Evidencia psicométrica - Tamayo-Agudelo, William Fernando; Zambrano-Cruz, Renato; Bell, Vaughan; Holguín-Lew, Jorge Carlos (Revista de Psicopatología y Psicología Clínica, 2016)
Abstract: The psychosis continuum: Psychometric evidence. This paper has two goals. The first is to determine the factor structure of the proneness to hallucination in a sample of the Colombian population using the Launay-Slade Hallucination Scale Revised (LSHS-R). The second goal is to compare the results of the non-clinical population with the results of a group of patients diagnosed with schizophrenia. The sample consisted of 230 persons, including 21 patients who were not in the active phase of the disease. The analysis found a two factor structure: Hallucinatory Experiences and Vivid Mental Events. Using Bayesian inference, we found credible differences between groups in the second factor and overlap in the values of the first factor. Resumen: Este trabajo tiene dos objetivos. El primero es determinar la estructura factorial de la propensión a la alucinación en una muestra de población colombiana general utilizando la Escala Revisada de Alucinaciones Launay-Slade (LSHS-R). Un segundo objetivo es comparar los resultados obtenidos en población general con los resultados obtenidos de un grupo de pacientes con diagnóstico de esquizofrenia. Participaron 230 personas, 21 de ellas pacientes que no se encontraban en fase activa de la enfermedad. La estructura encontrada fue de dos factores: Experiencias alucinatorias y Hechos mentales vívidos. Utilizando la inferencia bayesiana, se encontraron diferencias creíbles entre los grupos en el segundo factor y solapamiento en los valores del primer factor.